Stainless steel silver platinum electrode slurry and preparation method and application thereof

By adopting the composite and modification strategies of stainless steel powder, silver powder and platinum powder in the electrode slurry, combined with the optimized glass powder formula and inorganic carrier, the problem of insufficient conductivity and stability of traditional electrode slurry is solved, and higher conductivity and stability is achieved, suitable for high temperature and corrosion environments.

CN119786120AInactive Publication Date: 2025-04-08XIAN TENGXING ELECTRONIC TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510227995.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional electrode slurries have shortcomings in conductivity and stability, especially in high temperature and corrosive environments, which lead to degradation in electronic performance.

Method used

Stainless steel powder, silver powder and platinum powder are used to form a composite conductive powder, and the modified composite conductive powder is prepared by a specific modification method, combining an optimized glass powder formula, a suitable inorganic carrier and solvent to form a high-performance electrode slurry.

Benefits of technology

It significantly improves the conductivity and stability of the electrode slurry, enhances its durability in high temperature and corrosion environments, and improves the overall performance of electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode paste, and relates to stainless steel silver platinum electrode paste and a preparation method and application thereof. The stainless steel silver platinum electrode slurry provided by the invention comprises composite conductive powder, modified composite conductive powder, glass powder, an inorganic carrier and a solvent, wherein the composite conductive powder is composed of stainless steel powder, silver powder and platinum powder; the preparation method of the modified composite conductive powder comprises the following steps: adding a mixture of stainless steel powder, silver powder and platinum powder into a mixture of carboxymethyl cellulose, N-(beta-aminoethyl)-gamma-aminopropyltrimethoxysilane and polyvinyl alcohol, ultrasonically dispersing uniformly, reacting for 4-6 hours at the temperature of 100-110 DEG C, cleaning and drying, thereby obtaining the modified composite conductive powder. The glass powder is prepared from SiO2, H3BO3, Al2O3, CuO and IrO2; the inorganic carrier is zirconium oxide or beryllium oxide; the solvent is absolute ethyl alcohol or diisooctyl ether. The conductivity and the stability of the electrode paste are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode slurries and relates to a stainless steel silver-platinum electrode slurry and a preparation method and application thereof. Background Art

[0002] In the field of electronic materials, electrode slurry, as one of the key materials, is widely used in solar cells, fuel cells, capacitors and various electronic devices. The performance of electrode slurry directly affects the conductivity, stability and overall performance of electronic devices. Traditional electrode slurries mostly use a single metal powder as the conductive phase, such as silver powder, platinum powder, etc. Although these materials have a certain conductivity, the conductivity is not high, and the stability in specific environments (such as high temperature and corrosive environment) needs to be improved.

[0003] In order to improve the performance of electrode slurry, researchers have begun to try to compound multiple metal powders in recent years in the hope of achieving better conductivity, stability and cost-effectiveness. However, simple metal powder mixing often has problems such as uneven dispersion and weak bonding between particles, resulting in reduced conductivity and insufficient stability of electrode slurry.

[0004] Therefore, it is necessary to improve the formulation and preparation process of electrode slurry to improve its conductivity and stability. Summary of the invention

[0005] The present invention proposes a new electrode slurry and a preparation method thereof, aiming to solve the problems existing in the prior art. The stainless steel silver-platinum electrode slurry proposed in the present invention achieves a significant improvement in the performance of the electrode slurry through innovative composite and modification strategies, optimized glass powder formula, suitable inorganic carrier selection and optimized solvent selection, providing a new technical path for the development of the electronic materials field.

[0006] To achieve the above object, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a stainless steel silver-platinum electrode slurry, wherein the stainless steel silver-platinum electrode slurry comprises a composite conductive powder, a modified composite conductive powder, a glass powder, an inorganic carrier and a solvent; wherein: The composite conductive powder is composed of stainless steel powder, silver powder and platinum powder; The preparation method of the modified composite conductive powder is as follows: adding a mixture of stainless steel powder, silver powder and platinum powder to a mixture of carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol, uniformly dispersing by ultrasonication, reacting at 100-110° C. for 4-6 hours, and washing and drying to obtain the modified composite conductive powder; The glass powder consists of SiO2, H3BO3, Al2O3, CuO and IrO2; The inorganic carrier is zirconium oxide or beryllium oxide; The solvent is anhydrous ethanol or diisooctyl ether.

[0007] Preferably, in terms of weight percentage, the stainless steel silver-platinum electrode slurry comprises 68-73% composite conductive powder, 13-17% modified composite conductive powder, 2-4% glass powder, 5-8% inorganic carrier and 4-6% solvent.

[0008] Preferably, the weight ratio of stainless steel powder, silver powder and platinum powder in the composite conductive powder is 5-53:8-70:6-61.

[0009] Preferably, the weight ratio of stainless steel powder, silver powder and platinum powder in the modified composite conductive powder is 3-11:6-15:4-9.

[0010] Preferably, the weight ratio of carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol in the modified composite conductive powder is 1-2:3-6:0.5-1.5.

[0011] Preferably, the inorganic carrier is zirconium oxide.

[0012] Preferably, the solvent is anhydrous ethanol.

[0013] Preferably, in terms of weight percentage, the glass powder consists of 22-30% SiO2, 15-18% H3BO3, 13-20% Al2O3, 3-7% CuO and 2-6% IrO2.

[0014] In a second aspect, a method for preparing the stainless steel silver-platinum electrode slurry according to the present invention is provided, the preparation method comprising the following steps: After the components of the glass powder are evenly mixed, mixing, melting, crushing and ball milling are performed in sequence to obtain glass powder; The composite conductive powder, modified composite conductive powder, glass powder and solvent are uniformly mixed and then ground with an inorganic carrier to obtain a stainless steel silver-platinum electrode slurry.

[0015] Preferably, the preparation method comprises the following steps: After the components of the glass powder are uniformly mixed, the components are mixed in a three-dimensional mixer, melted in a high-temperature melting furnace, crushed in a roller press, and milled in a planetary ball mill to obtain the glass powder; The composite conductive powder, modified composite conductive powder, glass powder and solvent are uniformly mixed and then ground with an inorganic carrier in a three-roll grinder to obtain a stainless steel silver-platinum electrode slurry.

[0016] In a third aspect, there is provided an application of the stainless steel silver-platinum electrode slurry described in the present invention in improving the conductivity of the electrode slurry.

[0017] In a fourth aspect, there is provided an application of the stainless steel silver-platinum electrode slurry described in the present invention in improving the stability of the electrode slurry.

[0018] In a fifth aspect, there is provided an application of the stainless steel silver-platinum electrode slurry described in the present invention in improving the conductivity and / or stability of electronic devices.

[0019] In a sixth aspect, there is provided an application of the stainless steel silver-platinum electrode slurry described in the present invention in improving electrode performance, wherein the electrode performance is conductivity and / or stability.

[0020] In a seventh aspect, an electrode is provided, wherein the electrode is prepared from the stainless steel silver-platinum electrode slurry described in the present invention.

[0021] Compared with the prior art, the beneficial effects of the present invention are: The present invention uses stainless steel powder, silver powder and platinum powder to form a composite conductive powder, and prepares the modified composite conductive powder through a specific modification method [adding carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol for ultrasonic dispersion and reaction]. This composite and modification strategy not only improves the dispersibility of the metal powder, but also enhances the binding force between particles, thereby improving the conductivity and stability of the electrode slurry. At the same time, in combination with the inorganic carrier of the present invention, the conductivity and stability of the electrode slurry of the present invention are further improved. Specifically, carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol effectively improve the wettability and dispersibility of the surfaces of stainless steel powder, silver powder and platinum powder through chemical bonding and physical adsorption; ultrasonic dispersion and high temperature reaction further promote the uniform dispersion of the metal powder and the close bonding between particles, thereby improving the conductivity and stability of the electrode slurry. More specifically, zirconium oxide or beryllium oxide has good mechanical strength and chemical stability, can provide stable support and protection for electrode slurry, prevent metal powder from falling off or agglomerating during preparation and use; and can also protect the electrode from corrosion and oxidation.

[0022] The glass powder in the present invention is composed of SiO2, H3BO3, Al2O3, CuO and IrO2. The selection of these components helps to improve the high temperature resistance and corrosion resistance of the electrode slurry, and the high temperature resistance and corrosion resistance of the electrode slurry are further improved by optimizing the ratio of each component in the glass powder. SiO2, H3BO3, and Al2O3 can form a stable glass phase at high temperature to protect the metal powder from high temperature oxidation and corrosion. At the same time, the addition of CuO and IrO2 further improves the high temperature resistance and corrosion resistance of the glass powder.

[0023] The present invention selects anhydrous ethanol or diisooctyl ether as the solvent, which is beneficial to the uniform dispersion and coating of the electrode slurry.

[0024] In summary, the present invention achieves a significant improvement in the performance of the electrode slurry through innovative compounding and modification strategies, optimized glass powder formula, suitable inorganic carrier selection and optimized solvent selection, which is mainly due to the synergistic effect of composite conductive powder, modified composite conductive powder, glass powder, inorganic carrier and solvent. DETAILED DESCRIPTION

[0025] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0026] The technical scheme of the present invention is described below in conjunction with the examples, but the present invention is not limited to the following examples. The experimental methods and detection methods described in each example are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0027] Example 1 This embodiment provides a stainless steel silver-platinum electrode slurry, which comprises, by weight percentage, 68% composite conductive powder, 13% modified composite conductive powder, 2% glass powder, 5% inorganic carrier and 4% solvent; wherein, The composite conductive powder is composed of stainless steel powder, silver powder and platinum powder; the weight ratio of stainless steel powder, silver powder and platinum powder in the composite conductive powder is 5:8:6; The preparation method of the modified composite conductive powder is as follows: adding a mixture of stainless steel powder, silver powder and platinum powder to a mixture of carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol, uniformly dispersing by ultrasonication, reacting at 100° C. for 4 hours, washing with deionized water and drying to obtain the modified composite conductive powder; The weight ratio of stainless steel powder, silver powder and platinum powder in the modified composite conductive powder is 3:6:4; The weight ratio of carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol in the modified composite conductive powder is 1:3:0.5; The glass powder consists of 22% SiO2, 15% H3BO3, 13% Al2O3, 3% CuO and 2% IrO2; The inorganic carrier is beryllium oxide; The solvent is diisooctyl ether.

[0028] Example 2 This embodiment provides a stainless steel silver-platinum electrode slurry, which comprises, by weight percentage, 73% composite conductive powder, 17% modified composite conductive powder, 4% glass powder, 8% inorganic carrier and 6% solvent; wherein, The composite conductive powder is composed of stainless steel powder, silver powder and platinum powder; the weight ratio of stainless steel powder, silver powder and platinum powder in the composite conductive powder is 53:70:61; The preparation method of the modified composite conductive powder is as follows: adding a mixture of stainless steel powder, silver powder and platinum powder to a mixture of carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol, uniformly dispersing by ultrasonication, reacting at 110° C. for 6 hours, washing with deionized water and drying to obtain the modified composite conductive powder; The weight ratio of stainless steel powder, silver powder and platinum powder in the modified composite conductive powder is 11:15:9; The weight ratio of carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol in the modified composite conductive powder is 2:6:1.5; The glass powder consists of 30% SiO2, 18% H3BO3, 20% Al2O3, 7% CuO and 6% IrO2; The inorganic carrier is beryllium oxide; The solvent is anhydrous ethanol.

[0029] Example 3 This embodiment provides a stainless steel silver-platinum electrode slurry, which comprises, by weight percentage, 70% composite conductive powder, 16% modified composite conductive powder, 3% glass powder, 6% inorganic carrier and 5% solvent; wherein, The composite conductive powder is composed of stainless steel powder, silver powder and platinum powder; the weight ratio of stainless steel powder, silver powder and platinum powder in the composite conductive powder is 20:30:16; The preparation method of the modified composite conductive powder is as follows: adding a mixture of stainless steel powder, silver powder and platinum powder to a mixture of carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol, uniformly dispersing by ultrasonication, reacting at 110° C. for 6 hours, washing with deionized water and drying to obtain the modified composite conductive powder; The weight ratio of stainless steel powder, silver powder and platinum powder in the modified composite conductive powder is 6:11:7; The weight ratio of carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol in the modified composite conductive powder is 1.5:5:1; The glass powder consists of 28% SiO2, 16% H3BO3, 15% Al2O3, 5% CuO and 5% IrO2; The inorganic carrier is zirconium oxide; The solvent is anhydrous ethanol.

[0030] Example 4 This embodiment provides a method for preparing a stainless steel silver-platinum electrode slurry, the preparation method comprising the following steps: After the components of the glass powder are uniformly mixed, they are mixed in a three-dimensional mixer in sequence; smelted in a high-temperature smelting furnace at a smelting temperature of 1000-1100°C for a holding time of 1-2 hours; crushed in a roller press; and ball milled in a planetary ball mill at a speed of 200-350r / min for 3-5 hours to obtain glass powder; The composite conductive powder, modified composite conductive powder, glass powder and solvent are uniformly mixed and then ground with an inorganic carrier in a three-roll grinder at a speed of 100-300 r / min for 2-3 h to obtain a stainless steel silver-platinum electrode slurry.

[0031] Comparative Example 1 This comparative example is the same as Example 3, except that the carboxymethyl cellulose in the preparation method of the modified composite conductive powder is replaced by hydroxyethyl cellulose.

[0032] Comparative Example 2 This comparative example is the same as Example 3, except that zirconium oxide is replaced by titanium dioxide.

[0033] Comparative Example 3 This comparative example is the same as Example 3, except that the CuO in the glass powder is replaced by ZnO.

[0034] Comparative Example 4 This comparative example is the same as Example 3, except that no modified composite conductive powder is added.

[0035] Effect verification Experimental objects: Examples 1-3 and Comparative Examples 1-4: Stainless steel silver-platinum electrode slurry prepared according to Example 4; Experimental methods: The above stainless steel silver platinum electrode slurry was screen-printed on a 1206 specification alumina substrate, dried at 130°C for 15 minutes, and then cured at 150°C for 30 minutes to prepare a sample, and then the performance test was performed; Corrosion resistance test: Soak the sample in 20% dilute sulfuric acid solution for 96 hours, tear off the sample with 3M tape, and observe whether it falls off; High temperature resistance test: quickly heat the sample to 500°C, then quickly cool it down to observe whether the sample has cracks, deformation or falling off; Conductivity test: Use a four-probe resistivity / square resistance tester to test resistivity (uΩ·m); Experimental results: as shown in Table 1.

[0036] Table 1 Performance test results of each group of samples

[0037] In order to further demonstrate the effect of the present invention, the N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol in the preparation method of the modified composite conductive powder were replaced by other substances with similar properties, and the other conditions were consistent with Example 3. The results showed that the effect was equivalent to that of Comparative Example 1.

[0038] In order to further demonstrate the effect of the present invention, in the embodiment of the present invention, zirconium oxide is replaced by an organic carrier, and the organic carrier is obtained by dissolving ethyl cellulose resin in pine alcohol. The other conditions are consistent with those in Example 3. It is found that the effect is equivalent to that in Comparative Example 2.

[0039] In order to further demonstrate the effect of the present invention, the solvent in the present embodiment is replaced with terpineol, and the other conditions are consistent with those in Example 3. It is found that the effect is equivalent to that in Comparative Example 1.

[0040] It can be seen from Table 1 that each group of samples made from the stainless steel silver-platinum electrode slurry of the present invention has good conductivity. Specifically, with regard to conductivity, the resistivity of each group of samples made from the stainless steel silver-platinum electrode slurry of the present invention is relatively small, which is 80-90uΩ·m. Among them, Example 3 has the smallest resistivity and the best conductivity; while the resistivity of each group of samples in Comparative Examples 1-4 is relatively large, which is 162-191uΩ·m.

[0041] As can be seen from Table 1, the groups of samples made of the stainless steel silver platinum electrode slurry of the present invention have good stability in specific environments, such as high temperature and corrosive environments. Specifically, in a corrosive environment, the present invention has no shedding; while the groups of samples of comparative examples 1-4 have a large amount of shedding, which means that they cannot maintain sufficient durability in an acidic environment. In a high temperature environment, the present invention has no cracks, no deformation, and no shedding; while the groups of samples of comparative examples 1-3 have a large degree of deformation and shedding.

[0042] It can be seen that the present invention has both good conductivity and good stability. This is because the present invention uses stainless steel powder, silver powder and platinum powder to form a composite conductive powder, and prepares a modified composite conductive powder by a specific modification method [adding carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol for ultrasonic dispersion and reaction]. This composite and modification strategy not only improves the dispersibility of the metal powder, but also enhances the binding force between particles, thereby improving the conductivity and stability of the electrode slurry. At the same time, in combination with the inorganic carrier of the present invention, the conductivity and stability of the electrode slurry of the present invention are further improved. Specifically, carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol effectively improve the wettability and dispersibility of the surfaces of stainless steel powder, silver powder and platinum powder through chemical bonding and physical adsorption; ultrasonic dispersion and high temperature reaction further promote the uniform dispersion of metal powder and the close bonding between particles, thereby improving the conductivity and stability of the electrode slurry. More specifically, zirconium oxide or beryllium oxide has good mechanical strength and chemical stability, can provide stable support and protection for electrode slurry, prevent metal powder from falling off or agglomerating during preparation and use; and can also protect the electrode from corrosion and oxidation. Moreover, the glass powder in the present invention is composed of SiO2, H3BO3, Al2O3, CuO and IrO2. The selection of these components helps to improve the high temperature resistance and corrosion resistance of the electrode slurry, and the high temperature resistance and corrosion resistance of the electrode slurry are further improved by optimizing the ratio of each component in the glass powder. SiO2, H3BO3, Al2O3 can form a stable glass phase at high temperature to protect metal powder from high temperature oxidation and corrosion. At the same time, the addition of CuO and IrO2 further improves the high temperature resistance and corrosion resistance of the glass powder. Furthermore, the present invention selects anhydrous ethanol or diisooctyl ether as a solvent, which is conducive to the uniform dispersion and coating of the electrode slurry.

[0043] Through the effect verification experiment, it can be known that the formula system of the electrode slurry provided by the present invention is a whole. Specifically, the raw materials in the electrode slurry support each other functionally and have an interactive relationship. It is precisely because the raw materials support each other functionally and have an interactive relationship that the electrode slurry of the formula system of the present invention has good conductivity and stability.

[0044] It should be understood that the disclosed invention is not limited only to the specific method, scheme and material of description, because these all can change.It should also be understood that the terminology used herein is only for the purpose of describing specific embodiment scheme, rather than being intended to limit the scope of the present invention, and the scope of the present invention is only limited to the appended claims.

Claims

1. A stainless steel silver-platinum electrode slurry, characterized in that: The stainless steel silver-platinum electrode slurry comprises composite conductive powder, modified composite conductive powder, glass powder, inorganic carrier and solvent; wherein, The composite conductive powder is composed of stainless steel powder, silver powder and platinum powder; The preparation method of the modified composite conductive powder is as follows: adding a mixture of stainless steel powder, silver powder and platinum powder to a mixture of carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol, uniformly dispersing by ultrasonication, reacting at 100-110° C. for 4-6 hours, and washing and drying to obtain the modified composite conductive powder; The glass powder consists of SiO2, H3BO3, Al2O3, CuO and IrO2; The inorganic carrier is zirconium oxide or beryllium oxide; The solvent is anhydrous ethanol or diisooctyl ether.

2. The stainless steel silver-platinum electrode slurry according to claim 1, characterized in that: Calculated by weight percentage, the stainless steel silver-platinum electrode slurry includes 68-73% composite conductive powder, 13-17% modified composite conductive powder, 2-4% glass powder, 5-8% inorganic carrier and 4-6% solvent.

3. The stainless steel silver-platinum electrode slurry according to claim 1, characterized in that: The weight ratio of stainless steel powder, silver powder and platinum powder in the composite conductive powder is 5-53:8-70:6-61.

4. The stainless steel silver-platinum electrode slurry according to claim 1, characterized in that: The weight ratio of stainless steel powder, silver powder and platinum powder in the modified composite conductive powder is 3-11:6-15:4-9.

5. The stainless steel silver-platinum electrode slurry according to claim 1, characterized in that: The weight ratio of carboxymethyl cellulose, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and polyvinyl alcohol in the modified composite conductive powder is 1-2:3-6:0.5-1.

5.

6. The stainless steel silver-platinum electrode slurry according to claim 1, characterized in that: The inorganic carrier is zirconium oxide.

7. The stainless steel silver-platinum electrode slurry according to claim 1, characterized in that: The solvent is anhydrous ethanol.

8. The stainless steel silver-platinum electrode slurry according to claim 1, characterized in that: In terms of weight percentage, the glass powder consists of 22-30% SiO2, 15-18% H3BO3, 13-20% Al2O3, 3-7% CuO and 2-6% IrO2.

9. A method for preparing the stainless steel silver-platinum electrode slurry according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: After the components of the glass powder are evenly mixed, mixing, melting, crushing and ball milling are performed in sequence to obtain glass powder; The composite conductive powder, modified composite conductive powder, glass powder and solvent are uniformly mixed and then ground with an inorganic carrier to obtain a stainless steel silver-platinum electrode slurry.

10. A use of the stainless steel silver-platinum electrode slurry according to any one of claims 1 to 8 in improving electrode performance, characterized in that: The electrode properties are conductivity and / or stability.

Citation Information

Cited By

  • Preparation method and application of platinum powder for platinum-silver paste

    CN122231259A